The emergence of hepatitis E virus in Europe. (June 2015) - Sayed, Ibrahim M; Vercauteren, Koen; Abdelwahab, Sayed F; Meuleman, Philip
ABSTRACT : Hepatitis E virus (HEV) infections appear to be an emerging problem in Europe. Infections are mainly caused by viruses of genotype 3. Pigs and wild boar are the main reservoirs of HEV in Europe and most autochthonous infections are probably caused by the consumption of uncooked or undercooked infected meat. Nevertheless, transfusion-associated transmission has been described in different European countries but the efficiency of this route of transmission need to be further investigated. Most acute infections are asymptomatic or the induced symptoms are rather nonspecific. Although people that are otherwise completely healthy can spontaneously clear an HEV infection, people with underlying liver disease and/or suffering from immune deficiencies may require treatment to avoid chronicity and exacerbation of liver disease. In this review, we give an epidemiological overview of HEV in Europe and the potential complications.